2015
DOI: 10.1109/tthz.2015.2401392
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Terahertz Metamaterial Absorber Based on Asymmetric Resonators With Perfect Absorption

Abstract: In this paper, a broadband terahertz (THz) metamaterial absorber using asymmetric split ring resonator (ASR) was designed, fabricated, and characterized. By breaking the symmetry of a split ring resonator, two asymmetric resonances are excited from a dipole resonance, which enhance both the absorption and -factor. With the integration of four different ASRs into one unit cell, a broadband absorber experimentally obtained a 0.82-THz bandwidth with absorptivity of more than 0.9, which is 3.4 times as wide as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The signal greater than 95% can be absorbed by the device with SiO 2 thickness of t = 4 µm and metal diameter of d = 90 µm. This result can be interpreted from a normalized impedance extracted from the simulation [15,26]. For a sample with d = 90 µm and SiO 2 thickness of t = 4 µm, the imaginary and real parts of its normalized impedance are 0.04 and 0.95 respectively at a resonance frequency of 0.932 THz, as presented in Figs.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The signal greater than 95% can be absorbed by the device with SiO 2 thickness of t = 4 µm and metal diameter of d = 90 µm. This result can be interpreted from a normalized impedance extracted from the simulation [15,26]. For a sample with d = 90 µm and SiO 2 thickness of t = 4 µm, the imaginary and real parts of its normalized impedance are 0.04 and 0.95 respectively at a resonance frequency of 0.932 THz, as presented in Figs.…”
Section: Resultsmentioning
confidence: 80%
“…For example, Tao et al [17] experimentally showed a bi-layer THz MA composed of electrical ring resonator on cut wire in a reflection mode for the first time. Others have developed broadband THz MAs using methods such as a stack of many metamaterial layers, different material sizes in a unit cell, and a special pattern design in a unit cell [25][26][27][28]. In order to achieve frequency-adjustable absorption in a single device, the THz MAs with resonance frequency tunability are widely studied with different techniques such as those in the photoexcitation, liquid crystal, and thermal-based MAs [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…plasmonic sensor [1,2], broadband terahertz resonator [3], heat generation [4] and selective thermal emitters [5]. The impact of engineered metamaterial structures on negative index metamaterial absorbers (MAs) allows us to govern absorption peaks in specific spans of the electromagnetic (EM) spectrum [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this concern, one should mention perfect transmission in the deflection mode, 10,11 perfect one-way absorbers with high transmission in the neighboring bands, 12 and ultrathin, (nearly) perfect absorbers for various frequency ranges. [13][14][15][16][17][18][19][20][21][22] In spite of the fact that many absorbers were designed for terahertz frequencies, the potential of polar dielectrics in such devices has not yet been fully exploited. Clearly, absorption regimes achievable in more or less complex structures depend on the properties of the lossy materials that are comprised by these structures.…”
Section: Introductionmentioning
confidence: 99%